EDUCATIONAL VALUES FOR STUDENT CHARACTER BUILDING (A HERMENEUTIC ANALYSIS) - Desyandri Desyandri (Pedagogi: Jurnal Ilmu Pendidikan, 2016)
This article aims to discover, interpret, and identify the educational values embodied in the song of Minangkabau creation by NN. The identification process is done by a multidisciplinary hermeneutic analysis. Interpretation is generated by associating the aspects of language, music/songs, psychological, socio-cultural, and educational, so it can be identified seven (7) educational values. The educational values is a means to educate learners to perform the actions and behaviors that reflect proper Minang people. Education and learning as a means of cultural inheritance are obliged to explore, socialize, actualize, and cultivate the educational values on an ongoing basis in order to create learners who are well-mannered, civilized and noble character